KOMBUCHA TEA: A STUDY ON THE HALAL OF FERMENTED DRINKS - Dody Riswanto; Firman Rezaldi (International Journal Mathla’ul Anwar of Halal Issues, 2021)
Kombucha is a fermented beverage made from tea and sugar. Kombucha has benefits for the health of the body, this is due to various kinds of content including antioxidants, antibacterial, intestinal detoxification, lowering blood pressure and increasing body immunity. Kombucha is a drink that contains alcohol content at the end of the fermentation process. This is problematic because the majority of Indonesian consumers are Muslims who require halal food standards based on the regulations of the Indonesian Ulema Council (MUI). The research method used is a laboratory test with a treatment design that is designed based on chemical test procedures. The conclusion of the study is that based on the results of tests conducted at the health laboratory in the city of Tangerang, the results of the ethanol/alcohol content of 0.055 percent in kombucha drinks. Thus the test results have met the MUI regulations where fermented drinks must be below 0.5 percent to be declared a halal drink.